The Influence of Mudharabah, Musyarakah, Murabahah, Ijarah , and Istishna Financing on Profitability in Sharia People's Financing Banks in 2019-2022 - Yunika, Cindy Putri; Iqbal, Muhammad; Suryanto, Tulus; Kurniawan, Arif (IAIN Kendari, 2024)
Sharia People's Financing Bank is a bank that carries out business activities based on sharia principles and in its activities does not provide services in payment traffic. This research aims to determine the effect of mudharabah, musyarakah, murabahah, ijarah and istishna financing on profitability at Sharia People's Financing Banks in 2019-2022. The population in this study was 167 BPRS, through a purposive sampling technique with several predetermined criteria, a sample of 10 BPRS was obtained. This type of research is quantitative with panel data regression analysis using E-views 12 software. The results of this research show that the murabahah variable has a positive and significant effect on profitability at BPRS. This means that every increase or decrease in ROA affects the profitability of the Sharia People's Financing Bank. Meanwhile, the mudharabah, musyarakah, ijarah and istishna variables have no effect on profitability at BPRS. This means that every increase or decrease in ROA does not affect profitability.